AKUNTABILITAS DAN TRANSPARANSI PUBLIK KINERJA LEMBAGA NEGARA MELALUI SIDANG TAHUNAN MPR PERSPEKTIF KOMUNIKASI POLITIK - Harmonis Harmonis (SWATANTRA, 2017)
This  Paper  Aims  To  Describe  The  Significance  Or Significance  Of  Accountability  And  Public  Transparency Of The Performance Of State Institutions Through The Mechanism Of The Annual Session Of The People’s Consultative Assembly (Mpr) Viewed From The Point Of View Of Political Communication. The Main Theory Used In Addition To Organizational Communication, As Well As Political Communications That Occur In Political Institutions. This Study Is Included In The Study Of Library Research Or Literature Review By Reading And Analyzing Some References Or Study Materials Related To Building Accountable And Qualified State Institutions. The Results Of The Study Show That Every State Institution Has An Obligation To Become An Accountable And Transparent State Institution. The Foundation Is That The Community Or Stakeholders Associated With The State Institutions Desperately Need Information Relating To What The Performance Of The Institution Really Is, Then Provide Support For The Sustainability Of State Institutions In Particular And Nation State In General.